2017
DOI: 10.1016/j.ces.2017.04.040
|View full text |Cite
|
Sign up to set email alerts
|

A new numerical method for axial dispersion characterization in microreactors

Abstract: new numerical method for axial dispersion characterization in microreactors.(2017) Chemical Engineering Science, vol. 168. pp. 178-188. ISSN 0009-2509 Open Archive TOULOUSE Archive Ouverte (OATAO) OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. h i g h l i g h t sAn innovative numerical method for axial dispersion characterization is proposed. The method is validated thanks to a RTD experiment in a microchannel.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…It can thus be concluded that bend-induced vortices in combination with modulated flow velocities along the flow path are well able to generate a very small axial dispersion with the unit cell smallest hydraulic diameters between 5.5 and 9.3 mm for the given flow rate scale. The obtained axial dispersion coefficients could with the stated simplifications consistently be described by the correlation obtained by Moreau et al 65 which may open the way to estimate axial dispersion for a specific reactor configuration employed in a given process and may help to design additional plates. Proper numerical investigations could help to further verify the assumptions made, for example, for the curvature radii.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…It can thus be concluded that bend-induced vortices in combination with modulated flow velocities along the flow path are well able to generate a very small axial dispersion with the unit cell smallest hydraulic diameters between 5.5 and 9.3 mm for the given flow rate scale. The obtained axial dispersion coefficients could with the stated simplifications consistently be described by the correlation obtained by Moreau et al 65 which may open the way to estimate axial dispersion for a specific reactor configuration employed in a given process and may help to design additional plates. Proper numerical investigations could help to further verify the assumptions made, for example, for the curvature radii.…”
Section: Discussionsupporting
confidence: 61%
“…The results are compared in Figure 5b with experimentally observed D ax . The correlation derived by Moreau et al 65 is seemingly able to describe the experimental results obtained in this study despite the somewhat larger Re numbers based on the smallest cross section of the respective unit cell employed here. It is noted that considering center streamlines in the images of the unit cells, the above employed curvature radii were quite plausible but may be associated with uncertainties in the order of 30%.…”
Section: Methodsmentioning
confidence: 48%
See 1 more Smart Citation
“…Moreau et al 19 presented an original experimental method not‐frequently used up to now to estimate axial dispersion coefficients for a liquid flow. The method was validated thanks to an experiment in a millimetric channel.…”
Section: Introductionmentioning
confidence: 99%
“…The presented method is similar to the method reported by Moreau et al 19 However, in contrast to the example discussed there, we consider gas flow for two practical importance cases: empty and packed columns. In both cases, the method is helpful and predicts the coefficient values with good precision.…”
Section: Introductionmentioning
confidence: 99%